A mitochondrial-targeted peptide ameliorated podocyte apoptosis through a HOCl-alb-enhanced and mitochondria-dependent signalling pathway in diabetic rats and in vitro. (1st January 2019) - Wang, Xiaoqiao; Tang, Dongdong; Zou, Yaowei; Wu, Xiaoyu; Chen, Yihua; Li, Hongying; Chen, Siqi; Shi, Yue; Niu, Hongxin
Abstract: Mitochondria play important roles in the development of diabetic kidney disease (DKD). The SS peptide is a tetrapeptide that is located and accumulated in the inner mitochondrial membrane; it reduces reactive oxygen species (ROS) and prevents mitochondrial dysfunction. Podocytes are key cellular components in DKD progression. However, whether the SS peptide can exert renal protection through podocytes and the mechanism involved are unknown. In the present study, we explored the mechanisms of the SS peptide on podocyte injury in vivo and in vitro . Compared with the control group, the glomerular podocyte number and expression of WT1 were significantly reduced and TUNEL-positive podocytes were significantly increased in renal tissues in the diabetic rat. These effects were further exacerbated by hypochlorite-modified albumin (HOCl-alb) challenge but prevented by SS-31. In vitro, SS-31 blocked apoptosis in podocyte cell line induced by HOCl-alb. SS-31 prevented oxidative stress and mitochondria-dependent apoptosis signalling by HOCl-alb in vivo and in vitro, as evidenced by the release of cytochrome c (cyt c), binding of apoptosis activated factor-1 (Apaf-1) and caspase-9, and activation of caspases. These data suggest that SS-31 may prevent podocyte apoptosis, exerting renal protection in diabetes mellitus, probably through an apoptosis-related signalling pathway involving oxidative stress and culminating in mitochondria.